Feedback as a tool for academic independence: A study on EFL students’ research project writing at NUBTK - Shaikh, Hasan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study investigates feedback as a scaffolded, mediational process within the framework of Vygotsky’s Sociocultural Theory (SCT), examining its role in the research writing development of EFL students at the Northern University of Business and Technology Khulna (NUBTK). A cross-sectional survey was administered to 30 students who had completed EFL research projects in 2024, utilizing a 15-item online questionnaire. Descriptive analysis of the data reveals that feedback serves a dual mediational function: it scaffolds both structural coherence and linguistic accuracy while simultaneously facilitating the internalization of complex academic concepts, thereby fostering critical thinking and argumentation skills consistent with SCT's concept of guided cognitive challenge. The findings further indicate that verbal feedback is perceived as the most effective modality for synchronous, interactive mediation, whereas written feedback demonstrates greater variability in its perceived impact. Feedback also functions as a significant motivational and affective catalyst, bolstering student confidence and supporting their progression toward autonomous academic writing. The timeliness and individualization of feedback were identified as critical moderators of its perceived effectiveness. While this study offers insights into student perceptions, its generalizability is constrained by the cross-sectional design, reliance on self-reported data, and single-institution sample. The implications suggest the need for a balanced, multi-modal feedback regimen—integrating verbal, written, and technology-mediated approaches—aligned with SCT principles of scaffolding and gradual internalization. Future research should employ longitudinal designs and incorporate triangulated data from feedback providers to develop a more comprehensive understanding and to inform effective pedagogical policies and practices.